2021
DOI: 10.1177/01632787211015713
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Persian Version of the 11-Item de Jong Gierveld Loneliness Scale in Iranian Older Adults

Abstract: Loneliness is usually a chronic condition which may lead to physical and psychological undesirable consequences, and requires measurement and intervention. This study was conducted with the aim of preparing a Persian version of the 11-item de Jong Gierveld Loneliness Scale and evaluating its psychometric properties among the Iranian older adults. After applying the translation-back translation method, the prepared script was subjected to the face and content validity evaluations and a Persian version of the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 27 publications
0
17
0
2
Order By: Relevance
“…Los resultados del análisis factorial confirmatorio sugieren que la escala debe considerarse como bidimensional, con una distribución equitativa de ítems en ambos factores que representan a la soledad social y emocional, respectivamente. Estos resultados obtenidos coinciden con validaciones en diversos países (Ayala et al, 2012;Çavdar et al, 2015;De Holanda et al, 2018;Hosseinabadi et al, 2021;Ventura-León & Caycho-Rodríguez, 2017b); la estructura bidimensional de esta escala ofrece una novedad metodológica para los investigadores argentinos, ya que los instrumentos hallados hasta el momento en Argentina no operacionalizaban el constructo desde esta perspectiva bifactorial y la versión completa del instrumento que está siendo validada por Auné et al (2021) ostentó una estructura de un solo factor. Previamente se encontró que la soledad social y emocional, si bien están asociadas, son constructos diferenciales (Diehl et al, 2018) por lo que resulta relevante estudiarlos separadamente.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los resultados del análisis factorial confirmatorio sugieren que la escala debe considerarse como bidimensional, con una distribución equitativa de ítems en ambos factores que representan a la soledad social y emocional, respectivamente. Estos resultados obtenidos coinciden con validaciones en diversos países (Ayala et al, 2012;Çavdar et al, 2015;De Holanda et al, 2018;Hosseinabadi et al, 2021;Ventura-León & Caycho-Rodríguez, 2017b); la estructura bidimensional de esta escala ofrece una novedad metodológica para los investigadores argentinos, ya que los instrumentos hallados hasta el momento en Argentina no operacionalizaban el constructo desde esta perspectiva bifactorial y la versión completa del instrumento que está siendo validada por Auné et al (2021) ostentó una estructura de un solo factor. Previamente se encontró que la soledad social y emocional, si bien están asociadas, son constructos diferenciales (Diehl et al, 2018) por lo que resulta relevante estudiarlos separadamente.…”
Section: Discussionunclassified
“…La Escala de Soledad De Jong Gierveld (DJGLS, por sus siglas en inglés) presenta 11 ítems para operacionalizar la soledad emocional y social (De Jong Gierveld & Van Tilburg, 2010), la DJGLS fue adaptada y/o validada para su uso en diversos países, entre los que se encuentran España (Buz & Prieto, 2013;Buz et al, 2014), Perú (Ventura-León & Caycho-Rodríguez, 2017a), Irán (Hosseinabadi et al, 2021), Israel (Iecovich, 2013), Turquía (Çavdar et al, 2015) y Países Bajos (Uysal-Bozkir et al, 2015). Recientemente se halló un trabajo que reporta los primeros avances en el estudio de este instrumento en Argentina (Auné et al, 2021) pero aún son escasos los artículos que reportan en detalle su funcionamiento psicométrico en este país.…”
Section: Introductionunclassified
“…The following are some examples and is not an extensive list. The 11item version was found to be reliable and valid among older adults living in the community in Canada when administered in English (Penning, Liu & Chou, 2014), Spain when administered in Spanish (Buz & Pérez-Arechaederra, 2014), and Iran when administered in Persian (Hosseinabadi et al, 2021). The 6-item version was found to be reliable and valid among older adults living in the community in the Netherlands when administered in Dutch (de Jong-Gierveld & van Tilburg, 2006) and in Hong Kong when administered in Chinese (Leung, de Jong Gierveld & Lam, 2008).…”
Section: The De Jong Gierveld Loneliness Scalementioning
confidence: 93%
“…This is an 11-item questionnaire which scores social loneliness (5 items) and emotional loneliness (6 items) and is validated in Farsi ( 25 ). The content validity of the questionnaire based on Waltz and Bausell's content validity index was acceptable (0.881), and it had appropriate internal consistency (α: 0.778).…”
Section: Methodsmentioning
confidence: 99%
“…The content validity of the questionnaire based on Waltz and Bausell's content validity index was acceptable (0.881), and it had appropriate internal consistency (α: 0.778). Hosseinabadi R et al demonstrated that the Persian version of the 11-item De Jong Gierveld Scale had significant correlations with the Philadelphia Geriatric Center Morale Scale and also showed acceptable concurrent validity and reliability of this scale for measuring loneliness in Iranian older adults ( 25 ).…”
Section: Methodsmentioning
confidence: 99%